2019
DOI: 10.1111/efp.12558
|View full text |Cite
|
Sign up to set email alerts
|

A major facilitator superfamily transporter in Colletotrichum fructicola (CfMfs1) is required for sugar transport, appressorial turgor pressure, conidiation and pathogenicity

Abstract: The major facilitator superfamily (MFS) is one of the largest membrane‐protein families. To investigate the role of MFS proteins in the fungal plant anthracnose pathogen Colletotrichum fructicola, the CfMFS1 gene was deleted. This resulted in reduced mycelial growth, conidial yield and decreased virulence on tea oil camellia leaves. In addition, ∆Cfmfs1 showed increased sensitivity to osmotic stress and to a cell‐wall stressor. Further analysis revealed that CfMfs1 is required for conidial penetration and appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Anthracnose is one of the main diseases of Ca . oleifera , causing flowers, fruits, and buds to fall and even the whole plant to die, resulting in severe economic losses (Chen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Anthracnose is one of the main diseases of Ca . oleifera , causing flowers, fruits, and buds to fall and even the whole plant to die, resulting in severe economic losses (Chen et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…fructicola were studied. Previously, we had shown that CfSNF1 , CfSTE50 , CfMFS1 and CfHAC1 were involved in regulating growth, stress response and pathogenicity (Chen et al, 2019, 2020; Yao et al, 2019; Zhang et al, 2019). Shang et al (2020) studied the effector molecule CfEC92 of C .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The MFS1 gene of Colletotrichum lindemuthianum is only expressed at necrotrophic phase and is required for sugar utilization during interaction within the plant host [15]. In the Colletotrichum fructicola, the fungal pathogen of the tea oil camellia plant, the MFS transporter CfMfs1 has a role in sugar transport; in addition, the transporter also plays roles in conidiation and pathogenicity [16]. Bcmfs1 is involved in the protection of Botrytis cinerea against natural plant defense compounds during the pathogenic phase and antimicrobial compounds during its saprophytic growth phase [17].…”
Section: Introductionmentioning
confidence: 99%
“…The major facilitator superfamily (MFS) is one of the largest membrane transporter families currently known ( Chen et al, 2019 ). MFS’s diverse members are found in essentially all organisms in the biosphere.…”
Section: Introductionmentioning
confidence: 99%